الخطاب السياسي في القرآن :‏ ‏دراسة في تحليل الخطاب اعتمادا على المفردة القرآنية /‏ - إبراهيم، عبد الرحمن الحاج (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2011)
In this study, the researcher focuses on the political discourse in the Qur'an through discourse analysis approach on Qur'anic concepts, vocabularies, and their semantic network. Because of the current controversy on the extent of political concepts and perceptions in the Holy Qur'an, the researcher tries to estimate the dimensions of this political discourse. This study consists of two integral parts. In the first part, the researcher proposes a new methodology to analyze the Qur'anic discourse based on Islamic legacy and a range of contemporary scientific branches including Linguistics, Epistemology, Stylistic, and Narrative among others. This new methodology is presented in detailed steps and can be used in contemporary Qur'anic studies and analysis of its discourse. The second part studies the Qur'anic political theory and structure of political community including the Qur'anic model of structure of command. It also presents the power structure and the rules that regulate the relationship between the group of obedience and group of command. The researcher makes an attempt to discover the value system of political cross-objective criteria, and proposes an order of these values and the implications of their political concepts. The study concludes that the political project is not the first goal of the Qur'an. Because the Qur'an is a comprehensive changing project, the political project is part of the global project and the product of it at the same time. In addition, the religious concepts and perceptions of belief in the Qur'an have clear policy indications. The value of equality among human beings is the highest political value in the Qur'an, followed by human dignity.